Integrating Local Wisdom into Science Instruction to Strengthen Scientific Literacy: A Qualitative Study of a Rural Indonesian Junior High School - Merty Sari; Azizatul Khairi; Manap Somantri (Journal of Social Work and Science Education, 2026)
This qualitative descriptive study examined the integration of local wisdom into science instruction to strengthen students’ scientific literacy at SMP Negeri 1 Muara Rupit, a rural junior high school in South Sumatra, Indonesia. Participants included the principal, four science teachers, and ten students, selected purposively. Data were collected through classroom observations, semi-structured interviews, and documentation analysis (lesson plans, student worksheets, photographs) over four months. The interactive model of Miles, Huberman, and Saldaña guided data analysis. Findings revealed that local wisdom-based science instruction was implemented through planning, implementation, and evaluation stages. Teachers integrated local environmental contexts river ecosystems, agricultural activities, and local vegetation into learning objectives, instructional activities, and classroom discussions. This contextual approach enhanced students’ conceptual understanding, science process skills (observation, questioning, discussion), environmental awareness, and classroom engagement. However, the integration of comprehensive scientific literacy dimensions (evidence-based reasoning, systematic inquiry, analytical explanation) remained limited and unsystematic within instructional planning and assessment. Supporting factors included school leadership support, rich environmental resources, and student enthusiasm. Inhibiting factors comprised limited facilities, insufficient instructional time, and varying teacher readiness. The study concludes that local wisdom-based science instruction has significant potential to strengthen scientific literacy through contextual and meaningful learning experiences, but requires more systematic planning, scientific literacy-oriented assessment, and teacher professional development. Implications recommend designing structured local wisdom-based instructional frameworks and assessment instruments targeting higher-order scientific reasoning.